Tectonic imprints in Permian paleomagnetic data of Morocco - Weissbrodt, V.; Bachtadse, V.; Kirscher, Uwe; Saber, H.; Liu, Yebo; Ronchi, Ausonia (2024)
Although Pangea as Earth's youngest supercontinent has continuously served as a pivotal reference mark in paleogeographic reconstructions, its assembly is still a matter of debate. This is mainly due to poor paleomagnetic data coverage for Permian times for Africa, core element of Pangea. Paleomagnetic data from Adria, thought to be the African promontory in the Permian, yield paleolatitudes which, when compared to the European data set, result in a significant continental overlap and seem to confirm the original Pangea B concept of Irving (1977). In order to improve the paleomagnetic data situation for Africa, volcanic and sedimentary rocks were sampled in the Permo-Carboniferous basins of Morocco, yielding a total of 97 sites and 615 samples. Rock magnetic results are diagnostic for magnetite and hematite in various proportions as main carriers of the paleomagnetic signal. After removal of low and intermediate coercivity/blocking temperature components a characteristic component of magnetization pointing to the SE with declinations strung out along a small circle from 107° to 182° and with inclinations around −7° after tectonic correction was identified in 76% of the samples. In nine out of the ten basins studied, positive inclination only fold tests support the primary character of magnetization. Furthermore, three reversals were identified at the basins of M'Tal, Chougrane and Souk El Had Bouhsoussene lending further support to our interpretation of primary magnetization. VGPs are distributed along a NE-SW trending small circle band intersecting the Late Paleozoic segment of the Gondwana APWP with a rotation pole located in the sampling area. The resulting paleolatitudes yield a position of the Meseta block close to the paleo-equator at ∼280 Ma. The widespread presence of vertical axis rotations in the Meseta basins on the other hand, could be related to proposed intra-Pangea shear zones and would provide additional constraints on the extent of such shear zones towards the northern margin of Gondwana. However, tectonic models based on vertical axis rotations in this region need to be treated with caution, since the timing of these rotations remains ambiguous with the current data situation. Using our paleomagnetic data from the Meseta block as representative for Gondwana, a large latitudinal overlap between Gondwana and Laurussia is not required.